1999
DOI: 10.1002/(sici)1097-0290(19990920)64:6<698::aid-bit9>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

An inverse correlation between stress resistance and stuck fermentations in wine yeasts. A molecular study

Abstract: During alcoholic fermentations yeast cells are subjected to several stress conditions and, therefore, yeasts have developed molecular mechanisms in order to resist this adverse situation. The mechanisms involved in stress response have been studied in Saccharomyces cerevisiae laboratory strains. However a better understanding of these mechanisms in wine yeasts could open the possibility to improve the fermentation process. In this work an analysis of the stress response in three wine yeasts has been carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 43 publications
4
64
0
5
Order By: Relevance
“…The species that predominates on fermentative process for wine production is S. cerevisiae (Ivorra et al, 1999). During the fermentation the yeast produces ethanol, carbon dioxide and other secondary products important for flavor, taste and quality of wine serving as a reference on strain isolation (Lilly et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The species that predominates on fermentative process for wine production is S. cerevisiae (Ivorra et al, 1999). During the fermentation the yeast produces ethanol, carbon dioxide and other secondary products important for flavor, taste and quality of wine serving as a reference on strain isolation (Lilly et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…One of the changes that the yeasts face during the fermentation process is the progressive decrease in the essential nutrients for the growth, which demands permanent adjustment of genetics and the cellular metabolic system. The alcoholic fermentation also includes other stress conditions, such as osmotic pressure and the increasing of ethanol concentration (Ivorra et al 1999). The ethanol content may modify the degree of polarity of the cellular membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the suitability of marker gene expression as a tool for the study of yeast stress responses in industrial processes (13,16,21). In this work, we performed stress experiments and bench-top growth trials of wine yeast biomass production to demonstrate that the induction of specific stress-related genes may enable us to determine the environmental disturbances to which the cells are dynamically exposed.…”
mentioning
confidence: 98%